161k views
15 votes
Solve the following equation for y. Y= 2y+4y-3=27

Solve the following equation for y. Y= 2y+4y-3=27-example-1
User Jotaen
by
5.1k points

1 Answer

6 votes

Answer:


2y + 4y - 3 = 27 \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: 6y = 27 + 3 \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: 6y = 30 \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: y = (30)/(6) \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: y = 5

User Aminhotob
by
5.5k points